The 6G reconfigurable reflectarray antenna using a gold-VO-2 bilayer structure - Abbasi, Muhammad Inam; Qureshi, Suhail Asghar; Kamarudin, Muhammad Ramlee; Yamada, Yoshihide; Dahri, Muhammad Hashim; Zainal Abidin, Zuhairiah; Ramli, Nordin (Electromagnetics Academy, 2024)
A reconfigurable reflectarray antenna (RRA) with beam steering capability at 1.1 THz is proposed. The element of reflectarray is composed of vanadium dioxide (VO-2) and a gold bilayer model designed on a unit cell of 0.45λ, in which temperature variations produce different reflection phases due to the dependence of VO-2 on ambient conditions. The proposed reflectarray antenna has an aperture of 3100 µm. When particular cells of the array are exposed to temperature over 340 K, it causes the phase in those unit cells to alter, eventually acting as 1-bit RRA. The radiation pattern shows a maximum gain of 24.3 dBi and a side lobe level of −14.4 dB with an aperture efficiency of 21.7%. The maximum gain in case of offset is over 21 dBi with sidelobe levels less than −10 dB up to 80-degree beam steering range. The proposed reconfigurable reflectarray antenna shows a beam steering capability of up to 100 degrees, which is sufficient for indoor communications. The designed antenna with its performance is optimum for the development of 6G RIS-based communication systems.